Application of Magnetometry in Manto-type Copper Deposit Exploration, Case study: Meyami, Iran (Rudarsko-geološko-naftni zbornik, 2022)
This study has aimed to introduce a novel strategy for exploring the Manto-Michigan copper deposits, considered a principal copper resource after the porphyry type. Faults and crushed zones have a prominent role in this deposit type, and so we hope to detect unique patterns in magnetic responses that provide a helpful indicator to determine the mineralized zone. Accordingly, we want to test the magnetometry in Manto-type exploration. We performed a magnetometry survey in the Dochileh copper deposit that other researchers have claimed to be a Manto-Michigan type with a distance of 10 meters between survey lines and a spacing of 5 meters among stations on each profile. After processing the required maps, the residual magnetic map does not show any typical dipole magnetic anomaly, but some linear trends exist. One of those linear trends belongs to a faulted and crushed zone with a length of almost 2.5 km and different widths between 50 and 250 meters. The previous mineralized zones indicated by other prospectors who relied more on geological evidence in the Dochileh area have mostly stayed inside this negative value on the residual map. Four new boreholes were made in the negative anomaly to evaluate our hypothesis, and the derived cores confirmed the native copper, malachite, and cuprite mineralization.